Performance of Membrane Photocatalytic Reactor on Palm Oil Mill Secondary Effluent using zinc oxide –cymbopogon citratus (ZnO-CC) - Dilaeleyana; Hairom, Nur Hanis Hayati; Mohd Adnan, Raudah; Shamshul Afendi, Alisa; Abdul Rahman, Farah Afrina; Hisam, Norfadila Fazeri (Multidisciplinary Applied Research and Innovation, 2020)
Palm oil mill is one of the largest industries in Malaysia which could contribute for Malaysia’s economy. However, palm oil mill secondary effluent (POMSE) from this industry has created major disposal problem which could not be discharged to the environment due to its high biochemical oxygen demand (BOD), chemical oxygen demand (COD) and turbidity. Thus this present study aim to identify the performance of Zinc oxide-cymbopogon citratus (ZnO-CC) as the photocatalyst in the photocatalytic degradation process for POMSE treatment using membrane photocatalytic reactor (MPR). The performance of three different ZnO-CC nanoparticles (3:1, 5:1 and 9:1) in treating POMSE were successfully being observed and compared with commercial ZnO. The treated wastewater were analysed after membrane filtration process in terms of turbidity, pH, biochemical oxygen demand and chemical oxygen demand. The membrane surface of fouling layer was characterized using Field Emission Scanning Electron Microscopy  (FESEM). The result revealed that higher efficiency in removal of COD, BOD and turbidity in presence of ZnO-CC (3:1) (98-99%) of POMSE treatment using MPR. Thus, it is believed that this study have a potential on the improvement of MPR system and lead to an alternative methods for polishing process of POMSE.